Oology and the evolution of thermophysiology in saurischian dinosaurs: homeotherm and endotherm deinonychosaurians? - Grellet-Tinner, Gerald (Papéis Avulsos de Zoologia, 2006)
The origin of avian endothermy is a long-held question the answer of which cannot be provided by first level observations. Oological and reproductive characters have collectively provided a new source of data useful for phylogenetic analyses and paleobiological inferences. In addition, the observations of reproductive and oological evolutionary trends in saurischian dinosaurs lead to the interpretation that not only, the thermophysiology of these dinosaurs progressively became more avian-like but after re-examination allows to infer that deinonychosaurians represented here by three troodontids and one dromaeosaurid might already have developed an avian-like endothermy, thus predating the rise of avians. These results based on reproductive traits are independently corroborated by the discoveries of troodontid dinosaurs 1) in high latitudes, 2) covered with feathers in Chinese Lagerstätten, and recently 3) fossilized in a death pose identical to an avian sleeping posture.